2021
DOI: 10.1186/s12864-021-07672-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics analysis of differentially expressed genes in subcutaneous and perirenal adipose tissue of sheep as affected by their pre- and early postnatal malnutrition histories

Abstract: Background Early life malnutrition is known to target adipose tissue with varying impact depending on timing of the insult. This study aimed to identify differentially expressed genes in subcutaneous (SUB) and perirenal (PER) adipose tissue of 2.5-years old sheep to elucidate the biology underlying differential impacts of late gestation versus early postnatal malnutrition on functional development of adipose tissues. Adipose tissues were obtained from 37 adult sheep born as twins to dams fed ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 93 publications
0
16
0
Order By: Relevance
“…Research on energy restriction during late gestation and the muscle and blood transcriptome of beef calves revealed that impaired glucose metabolism may affect genes involved in cellular respiration, including ETFRF1 [ 58 ]. ETFRF1 was also listed among the genes that were dysregulated in subcutaneous and perirenal adipose tissue of sheep as a resultant of pre- and early postnatal malnutrition [ 59 ]. In the current research, ETFRF1 expression was downregulated as a consequence of the diminished SLC2A8 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Research on energy restriction during late gestation and the muscle and blood transcriptome of beef calves revealed that impaired glucose metabolism may affect genes involved in cellular respiration, including ETFRF1 [ 58 ]. ETFRF1 was also listed among the genes that were dysregulated in subcutaneous and perirenal adipose tissue of sheep as a resultant of pre- and early postnatal malnutrition [ 59 ]. In the current research, ETFRF1 expression was downregulated as a consequence of the diminished SLC2A8 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous molecular mechanisms associated with fat metabolism in sheep have been investigated [ 3 , 11 , 35 ]. However, the genetic mechanism at the transcriptional level of fat metabolism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Gene transcripts undergo diverse splicing to generate various isoforms. With the commercialization of sequencing platforms and the reduced sequencing costs, transcriptome sequencing technology has found widespread application in animal transcriptome studies, including pigs [ 7 ], chickens [ 8 ], beef cattle [ 9 ], goats [ 10 ], and sheep [ 11 ]. Previous studies on sheep fat metabolism have primarily focused on short-read RNA-seq data from second-generation sequencing platforms [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large animal models such as sheep have previously been used to investigate the interplay between insulin sensitivity, type II diabetes, and metabolic response to exercise and adiposity ( 7 9 ). Similarly, using the Copenhagen sheep model, we have previously demonstrated significant changes in the PER transcriptome of 2.5-yr-old adults exposed to prenatal undernutrition (LOW) followed by a mismatching obesogenic, high-carbohydrate-high-fat (HCHF) diet during the first 6 mo of life (adolescent lambs) ( 10 ). In these nutritionally mismatched LOW-HCHF adult sheep, the affected molecular pathways included cholesterol metabolism, whereas early postnatal HCHF feeding targeted biological processes related to kidney cell differentiation.…”
Section: Introductionmentioning
confidence: 97%